Asian cross-border marriage migration : demographic patterns and social issues - Yang, Wen-Shan; Lu, Melody Chia-Wen (IIAS publications series. Edited volumes, 2010)
"Asian Cross-border Marriage Migration: Demographic Patterns and Social Issues is an interdisciplinary and comparative study on the rapid increase of the intra-Asia flow of cross-border marriage migration. This book contains in-depth research conducted by scholars in the fields of demography, sociology, anthropology and pedagogy, including demographic studies based on large-scale surveys on migration and marital patterns as well as micro case studies on migrants' living experiences and strategies. Together these papers examine and challenge the existing assumptions in the immigration policies and popular discourse and lay the foundation for further comparative research."--Page 4 of cover.